EKSPLORASI RHIZOBAKTERI INDIGENOUS TANAMAN CABAI RAWIT (Capsicum frustescens Linn.) DARI PERTANIAN SEMI ORGANIK DESA BATUR KABUPATEN SEMARANG SEBAGAI AGEN HAYATI PENGENDALI PERTUMBUHAN JAMUR Fusarium oxysporum f.sp capsici - M Eka Prastya; Agung Suprihadi; Endang Kusdiyantini (Jurnal Akademika Biologi, 2014)
Rhizobacteria is a group of bacteria that live in the around of plant roots. This type of bacteria known have the ability to stimulate plant growth by producing growth hormone, as well as to inhibit the growth of plant pathogens synthesize compounds with antibiotics or extracellular enzymes. The purpose of this study was to obtain and describe the morphological, biochemical and genetic isolates rhizobacteria of semi-organic farmland Semarang District village Batur which has the ability as a biological control agent of fungal pathogens Fusarium oxysporum f.sp capsici. The results obtained fifteen isolates the majority rhizobacteria bacilus shaped gram-positive and classified. Rhizobacteria inhibition test capabilities against pathogenic fungi was performed using dual culture test and test biomass. Dual culture test results showed that the inhibition of isolates E1 has a 3.77%, 1.88% isolates E3 and E15 isolates 22%. The biomass tests show E15 isolates capable of inhibiting the growth of pathogenic fungi best with the smallest weight of fungal biomass 0.0386 grams. The results of the molecular characterization based on 16S rRNA gene sequences to known that E15 isolates has similar with Bacillus cereus strain ATCC 14579 with similarity of 97%. The results of the biochemical characterization of isolates E15 has similarities with B. cereus species that is catalase positive, motile, have endospores, is able to hydrolyze starch and ferment glucose.Keywords: rhizobacteria, Fusarium oxysporum f.sp capsici, gen 16S rRNA, Bacillus cereus